Incidence of Antimicrobial-Resistant Escherichia coli in Uropathogenic Infections: An Emerging Therapeutic Dilemma - Wajid, Dr. Arslan; Anwar, Paris; Ikhtiar, Farhan; Saeed, Hooria; Wajid, Usman (Journal of Basic and Emerging Sciences, 2025)
The purpose of this study was to determine the frequency of multi-drug-resistant E. coli in patients with UTIs who were seen at the Pakistan Institute of Medical Sciences' General Medicine Department. During the course of six months, a total of 800 urine samples were taken from both indoor and outdoor patients attending the PIMS laboratory. Of these samples, 150 tested positives for urinary tract infections. After that, these samples were examined utilizing various culture media. Urine samples were cultured on CLED Agar media to determine the presence of bacteria, and then the biochemical test API 10, which is often used to identify gram negative bacteria, was performed. After bacterial growth was observed in the samples, MHA medium was added to determine the antibiotics' sensitivity or susceptibility using an antibiotic disc. Following that, the results were documented, with over three medications exhibiting resistance to the tested antibiotics being ruled out as MDR. Out of 150 samples, 100 tested positive for MDR, whereas the remaining 50 did not. Of the agents examined, levofloxacin (62.7%), amoxicillin/clavulanic acid (74.7%), and cefepime (70%) showed the most resistance, whereas tazobactam (18.7%), amikacin (16%), and Fosfomycin (15.3%) showed the lowest resistance. The other examined medicines in the current investigation included ceftriaxone 43.3%, ampicillin 54%, cefepime 70%, sulbactam 24.7%, and cotraimaxloe 47.3%. Resistance to norfloxacin is 54% and Fosfomycin is 15.3%, respectively. In conclusion, the rising prevalence of multidrug-resistant E. coli underscores the urgent need for antimicrobial stewardship programs (ASPs). By promoting appropriate antibiotic use, enforcing strict prescription guidelines, conducting regular audits, and fostering collaboration among healthcare professionals, we can mitigate resistance, enhance treatment outcomes, and preserve the efficacy of existing antibiotics.